KEANEKARAGAMAN BIVALVIA DI PESISIR PANTAI PAYUMB KELURAHAN SAMKAI DISTRIK MERAUKE - Lely Kustiyarini; Irba Djaja (Universitas Musamus, Merauke, Papua, 2011)
Bivalves is one class of the phylum Mollusca and is one of the non-living resources of fish that have high diversity. Research on